INCOME FROM NON-EXCHANGE TRANSACTIONS IN DELI SERDANG REGENCY 2022-2023 - Haholongan Sihombing, Siti Rachel; Manihuruk, Aldi Johannes; Muda, Iskandar (JIAR : Journal Of International Accounting Research, 2025)
This study analyzes non-exchange transactions in Deli Serdang Regency for the 2022 and 2023 fiscal years based on official Local Government Financial Statements (LKPD) and Audit Board (BPK) reports. Non-exchange transactions such as grants, taxes, subsidies, and social assistancerepresent government revenues and expenditures without direct exchange of equal value. The research uses secondary data from regional budget documents, financial repor ts, and relevant literature to understand their structure, implementat ion, and impact. Findings indicate that non-exchange transactions play a crucial role in funding infrastructure, education, health, and welfare programs. Deli Serdang Regency achieved a high level of accountability, as reflected in the Wajar Tanpa Pengecualian (Unqu alified Opinion) for both years. However, dependence on central gov ernment transfers remains high, while local revenue generation and social assistance disbursements highlight ongoing fiscal challenges. The study recommends strengthening governance, adopting digital financial systems, and increasing community participation in oversig ht to enhance transparency and efficiency in managing public funds